Islamic Law in the Marriage Tradition Banjar Community - Al Amruzi, M. Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This paper was written to study the marriage traditions that exist in Banjar society, then to photograph and study them with Islamic law, especially in the field of marriage law. The results of the study show the existence of marriage traditions in the Banjar community which begin with finding and determining prospective brides and grooms with basasuluh and continued with badatang. Then continued with the tradition of bapayuan and bapatut Jujuran in determining the marriage and then bapatut Jujuran is carried out in determining what and how much the marriage dowry is. After that it is continued with maantar Jujuran and the marriage contract which was previously started with the tradition of manurunakan and maarak the groom to the place of the marriage contract and wedding reception and continued with the tradition of the bridegroom Batatai. These traditions are very much in accordance with the concept of Islamic law; the tradition of basasuluh is in accordance with the concept of ta'aruf, badatang with the concept of khitbah, the tradition of bapayuan and bapatut Jujuran is very much in line with the concept of easy and cheap dowry so as not to hinder marriage. The tradition of maantar Jujuran and the marriage contract is to ensure the existence of a dowry and the amount of dowry given and stated in the marriage contract, while the tradition of manurunakan and maarak the groom and the tradition of the bride and groom are in order to ensure the validity of the marriage that can be witnessed and assessed by the wider community that the bride and groom are not included among those who are hindered and prohibited from marriage.